2019
DOI: 10.1016/j.jhepr.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Platelets in chronic liver disease, from bench to bedside

Abstract: In the last decade, numerous studies revealed physiologic and pathophysiologic roles of platelets beyond haemostasis, a process to prevent and stop bleeding. These include the activation of the immune system and the promotion of inflammation, infection and cancer. Hence, the emerging view on the role of platelets has shiftedplatelets are now seen as alert "sentinels" of the immune compartment, rather than passive bystanders. Herein, we review well-established and newly discovered features of platelets that def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 110 publications
2
36
0
Order By: Relevance
“…Possible causes include splenic sequestration of platelets, suppression of platelet production in the bone marrow, decreased thrombopoetin production in the liver and an autoimmune mediated destruction[ 5 ]. Additionally, platelets actively participate in pathophysiologic processes in the liver, resulting in fibrosis and cirrhosis; previous studies including animal models showed that platelets have a major role in liver inflammation via interactions with the hepatic sinusoidal endothelium and myeloid cells, inducing diverse hepatic processes ranging from liver repair and regeneration to necroinflammation and fibrosis[ 10 , 11 ]. Additionally, studies hypothesized that circulating platelet-neutrophil aggregates can induce neutrophil activation, thus driving end organ damage in patients with cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…Possible causes include splenic sequestration of platelets, suppression of platelet production in the bone marrow, decreased thrombopoetin production in the liver and an autoimmune mediated destruction[ 5 ]. Additionally, platelets actively participate in pathophysiologic processes in the liver, resulting in fibrosis and cirrhosis; previous studies including animal models showed that platelets have a major role in liver inflammation via interactions with the hepatic sinusoidal endothelium and myeloid cells, inducing diverse hepatic processes ranging from liver repair and regeneration to necroinflammation and fibrosis[ 10 , 11 ]. Additionally, studies hypothesized that circulating platelet-neutrophil aggregates can induce neutrophil activation, thus driving end organ damage in patients with cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…The general downregulation of ‘Platelet activation’ (Additional File 5 ) broadly agreed with this scenario, since liver dysfunction is usually reported in combination with an activation of platelets, often considered dynamic sentinels interacting with immune cells [ 134 – 136 ]. In this context, the marked upregulation of M-SAA3.2 ( Mammary Serum Amyloid A3.2 ) [FC = 5.70] was noteworthy (Table 8 ).…”
Section: Discussionmentioning
confidence: 72%
“…This common programme is very similar to human NAFLD and NASH (Teufel et al 2016). Downregulation of fatty acid metabolism and positive enrichment of platelets and haemostasis-related pathways is a hallmark of our data as well as transcriptomes of human NASH (Arendt et al 2015; Mardinoglu et al 2014; Moylan et al 2014; Ramadori et al 2019; Naguib et al 2020).…”
Section: Discussionmentioning
confidence: 76%